2018
DOI: 10.1016/j.ecoenv.2018.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Selenium protects rice plants from water deficit stress

Abstract: Selenium (Se) is essential to humans and animals due to its antioxidant properties. Although it is not considered an essential nutrient for higher plants. Many studies show that Se in low concentrations (up to 0.5 mg kg) provides beneficial effects to non-hyperaccumulating plants by participating in antioxidant defense systems and enhancing tolerance to abiotic stress. Therefore, this study aimed to evaluate the effects of Se application rates on rice plants under different soil water conditions. The experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(43 citation statements)
references
References 50 publications
3
31
0
Order By: Relevance
“…that the chilling stress decreased the Na + content in rice plants as well (Figure 4a). A similar decrease of Na + and K + contents was observed under various abiotic stress conditions [67,68,69,70]. Furthermore, nonstressed plants treated with NO showed higher accumulation of Ca 2+ and Mg 2+ , which indicated that NO might upregulate the divalent cations uptake capacity of rice plants which led to the further enhancement of plant growth (Table 1; Figure 4c, d).…”
Section: Discussionsupporting
confidence: 69%
“…that the chilling stress decreased the Na + content in rice plants as well (Figure 4a). A similar decrease of Na + and K + contents was observed under various abiotic stress conditions [67,68,69,70]. Furthermore, nonstressed plants treated with NO showed higher accumulation of Ca 2+ and Mg 2+ , which indicated that NO might upregulate the divalent cations uptake capacity of rice plants which led to the further enhancement of plant growth (Table 1; Figure 4c, d).…”
Section: Discussionsupporting
confidence: 69%
“…After submission of this manuscript multiple publications described the beneficial effects of Se on abiotic stress tolerance in rice. Se application protects rice plants from water deficit stress (Andrade et al, 2018), since rice plants treated with Se showed a higher net photosynthesis, water use efficiency and antioxidant activities. Moulick et al (2018) reported the influence of Se in mitigating arsenic induced phytotoxicity in rice.…”
Section: Discussionmentioning
confidence: 99%
“…Se fertilization is a relatively low-cost approach to the prophylaxis of consumers against nutrient deficiency. Several countries, such as Finland, Malawi, Australia, and New Zealand, have supported this strategy through biofortification programs, demonstrated to boost Se content in human tissue and body fluids of the population (Arthur, 2003; Eurola et al, 2004; Chilimba et al, 2012), as well as Brazil, where studies were performed on upland rice (Reis et al, 2018), rice (Andrade et al, 2018) and cowpea (Silva et al, 2018b; Silva et al, 2019).…”
Section: Introductionmentioning
confidence: 99%